Integração entre gestão de pessoas e marketing como componente da orientação para o mercado no contexto da indústria 4.0: um estudo comparativo regional - Fernandes, Núbia Cristina (2022)
Market orientation is part of a marketing subject related to market intelligence in organization generation, both in terms of organization generation for processes and cultural aspects, creation and customer planning. Therefore, cross-functional integration becomes essential. However, the current Industry 4.0 scenario may require brand new types of cross-functional integration between people with technology, machines with machines, people with people. The objective of this research is propose a model for analyze how HR initiatives of cross-functional integration between Marketing and peer functions can contribute to market orientation in the context of Industry 4.0. As a methodology, this research is a descriptive study, with a quantitative approach, since primary data were collected through a virtual questionnaire. Non probabilitstic sampling was used and for data analysis. Structural Equation Modeling was used to verify the relationship between the variables. As conclusions, we found that the HR efforts to integrate internal areas can generate market orientation directly, and also indirectly, through the support of industry 4.0 technologies. In addition to these results, the regional maturity level in the implementation of Industry 4.0 technologies was analyzed, taking into account the growth in the implementation of such technologies in the Triângulo Mineiro region, where part of the data collection was carried out. In this way, it was possible to highlight the comparative aspects between the management actions in the Triângulo Mineiro in relation to the other regions surveyed.